การวิเคราะห์โครงสร้างตลาดและปัจจัยที่เป็นตัวกำหนดราคาผลิตภัณฑ์กาแฟพร้อมดื่ม - แสวงกุล, สมภูมิ (Journal of Business, Innovation and Sustainability (JBIS), 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาโครงสร้างตลาดและพฤติกรรมการแข่งขันของตลาดผลิตภัณฑ์กาแฟพร้อมดื่มและปัจจัยที่เป็นตัวกำหนดราคาผลิตภัณฑ์กาแฟพร้อมดื่มภายในประเทศไทย โดยใช้วิธีการวิจัยแบบผสมผสาน โดยการวิจัยเชิงปริมาณอาศัยข้อมูลราคาและคุณลักษณะของผลิตภัณฑ์กาแฟพร้อมดื่มที่วางจำหน่ายในร้านค้าปลีกสมัยใหม่แห่งหนึ่งในเขตปริมณฑลของกรุงเทพมหานคร ในช่วงระหว่างเดือนพฤศจิกายน 2557 - มกราคม 2558 นำมาวิเคราะห์ข้อมูลด้วยแบบจำลองราคาฮีดอนนิค การวิเคราะห์การถดถอยแบบพหุคูณด้วยเทคนิควิธีกำลังสองน้อยที่สุด และการวิจัยเชิงคุณภาพอาศัยการสัมภาษณ์เชิงลึกกลุ่มตัวอย่างผู้ประกอบการผลิตภัณฑ์กาแฟพร้อมดื่มจำนวน 5 ราย ผลการวิจัยพบว่า ค่าดัชนีเฮอร์ฟินดัลฯแสดงให้เห็นถึงตลาดผลิตภัณฑ์กาแฟพร้อมดื่มมีโครงสร้างตลาดเป็นแบบผู้ขายน้อยราย มีรูปแบบการแข่งขันที่ไม่ใช้ราคาเป็นกลยุทธ์หลัก สำหรับผลการวิเคราะห์สมการถดถอยแบบพหุคูณกับผลิตภัณฑ์กาแฟพร้อมดื่มในตลาด 400 ผลิตภัณฑ์ด้วยวิธีการเลือกตัวอย่างแบบสองขั้นตอน พบว่า ปัจจัยที่มีผลเชิงลบต่อราคาผลิตภัณฑ์คือ ระดับกาแฟสกัด ในขณะที่ปัจจัยที่มีผลเชิงบวกต่อราคาผลิตภัณฑ์ ได้แก่ ระดับผงโกโก้ ยี่ห้อ ระดับแอลคาร์นิทีน ระดับสารให้ความหวานแทนน้ำตาล ระดับน้ำตาล ระดับโครเมียมอะมิโนแอซิดคีเลต ระดับนมผง และระดับนมสด ตามลำดับ โดยปัจจัยทั้งหมดสามารถอธิบายความแปรปรวนของราคาผลิตภัณฑ์กาแฟพร้อมดื่มได้ร้อยละ 80.7 ผลการศึกษาชี้ให้เห็นว่า ผู้บริโภคจ่ายราคาส่วนเพิ่มให้กับข้อมูลคุณค่าทางโภชนาการ และตราสินค้าที่ได้รับความนิยม Analysis of Market Structure and Factors Determining the Prices of Ready-to-Drink Coffee Products This research had two main objectives; to study market structure and competitive behavior of ready-to-drink coffee market, and to study factors determining the prices of ready-to-drink coffee products in Thailand. Mixed methods were employed in this research. A quantitative approach was used to obtain the data of different ready-to-drink coffee products. The data were collected from a modern retail trade store during November 2014 - January 2015. The hedonic price model and multiple regression analysis (OLS technique) were applied in the analysis. A qualitative method was used to collect the data through in-depth interviewing of 5 selected entrepreneurs in ready-to-drink coffee products. The findings indicated that HHI showed that the ready-to-drink coffee market was an oligopoly market, which competed by a non-price method as a core strategy. The results of a multiple regression analysis, based on the 400 ready-to-drink coffee products in the market were selected by two-stage sampling, revealed that the negative factor determining the price was coffee extract level. Meanwhile the positive factors were; cocoa powder level, brands, L-carnitine level, Sugar substitute level, sugar level, chromium amino acid chelate level, powdered milk level, and fresh milk level, respectively. The Adjusted R2 indicated that the model explained 80.7 percent of the variability of the price. The results indicated that consumers paid premium prices for some popular attributes, i.e. nutrition information, and brands. DOI: http://dx.doi.org/10.14456/becj.2016.4